3D printing of pharmaceuticals for disease treatment - Chakka, L. R. Jaidev; Chede, Shanthi (Frontiers in Medical Technology, 2023)
developing and manufacturing pharmaceuticals in a personalized manner for patients with high volume and rare diseases. The traditional pharmaceutical manufacturing process involves the utilization of various excipients to facilitate the stages of blending, mixing, pressing, releasing, and packaging. In some cases, these excipients cause serious side effects to the patients. The 3D printing of pharmaceutical manufacturing avoids the need for excessive excipients. The two major components of a 3D printed tablet or dosage form are polymer matrix and drug component alone. Hence the usage of the 3D printed dosage forms for disease treatment will avoid unwanted side effects and provide higher therapeutic efficacy. With respect to the benefits of the 3D printed pharmaceuticals, the present review was constructed by discussing the role of 3D printing in producing formulations of various dosage forms such as fast and slow releasing, buccal delivery, and localized delivery. The dosage forms are polymeric tablets, nanoparticles, scaffolds, and films employed for treating different diseases.